Знаменитые женщины: биографический справочник / Е. Н. Обоймина, О. В. Татькова - Обоймина Е.Н. (Электронная книга, 2005)
Экземпляры: (20080424) / Инвентарный номер: 44758 / Цена: 190.57 / Сис.шифр: 92 44758 / Авт.знак: О-21 / ББК: 92